2020
DOI: 10.3390/su12155893
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Healthy Lifestyle through Basic Psychological Needs in Inactive Adolescents: A Protocol Study from Self-Determination Approach

Abstract: Prevalence of overweight and obesity is an important health problem worldwide. It was shown that physical activity and sedentary behaviour are associated with prevalence of overweight and obesity in youth individuals. However, few children and adolescents meet the World Health Organization recommendations about physical activity levels. The need to start promoting regular physical activity from an early age is crucial to avoid these problems. Therefore, the aim of the current research is to show a school-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 75 publications
0
11
0
Order By: Relevance
“…The present cross-sectional study was developed within a project aimed at promoting healthy behaviours among youth [ 35 ]. The baseline data were collected, before the COVID-19 pandemic, from March to June 2019 in Extremadura (Spain).…”
Section: Methodsmentioning
confidence: 99%
“…The present cross-sectional study was developed within a project aimed at promoting healthy behaviours among youth [ 35 ]. The baseline data were collected, before the COVID-19 pandemic, from March to June 2019 in Extremadura (Spain).…”
Section: Methodsmentioning
confidence: 99%
“…Based on the 15 studies from English-speaking countries that were examined, it seems that many schools are not promoting active lifestyles effectively for their students. Many of the studies that focused on effective strategies for promoting active lifestyles also reported that schools are currently Teachers and Curriculum, Volume 23, Issue 1, Special Issue: Ngā Timatanga Hou: Fresh Perspectives on Education, 2023 not promoting active lifestyles effectively (Cale et al, 2016;Martins et al, 2018;Mizdrak, 2021;Sánchez-Miguel et al, 2020;Shull et al, 2020;Wojtyła-Buciora et al, 2014;Wood & Hall, 2015). This further highlights the importance of the major theme identified in this review.…”
Section: Current Promotion Of Active Lifestylesmentioning
confidence: 62%
“…Cross-sectional data from the physical activity and healthy habits promotion in adolescent's project was analyzed for this study. 38 Data was collected from March to June 2019, in a city in southwestern Spain. Simple random sampling was used.…”
Section: Design and Participantsmentioning
confidence: 99%